Emergency clinical path of ST Elevation Acute Myocardial Infarction - Tiziano Lenzi; Nicola Parenti; Cesare Antenucci; Mauro Metalli (Emergency Care Journal, 2007)
ST Elevation Acute Myocardial Infarction (STEMI) represents a clinical condition that witnessed a new therapeutic progress in the last years, from thrombolysis era to primary percutaneous coronary intervention (PPCI) era. New European and North American guidelines and the Consensus document produced from Italian Cardiologist Federation (FIC) with Emergency Physicians (SIMEU) and Territorial System of Emergency 118 (SIS 118) require clinical and organized pathway with the involvement of Cardiologist, in and out hospital Emergency Physicians and 118. Main aim is to develop a network able to give to all patients the best treatment in the shortest time. The efficiency and functionality of these pathways must be verified through evaluation systems. The Imola’s experience confirms as the network can be put into practice and that it’s possible to analyse and to develop models of improvement.